Open Market Operations as a Monetary Policy Shock Measure in a Quantitative Business Cycle Model - Burkhard Heer; Andreas Schabert (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper presents a business cycle analysis of monetary policy shocks measured by disturbances to open market operations, i.e. the ratio of open market papers to non-borrowed reserves. We find empirical evidence for the usefulness of this policy measure, as it predicts significant declines in output, M1 growth, and prices, as well as a significant rise in interest rates after a monetary contraction. We develop a dynamic general equilibrium model with financial intermediation where monetary policy is conducted via open market operations. In accordance with our empirical findings, a monetary tightening leads to a fall in output, monetary aggregates, and factor prices. In contrast to an alternative model specification with money growth shocks, our model with disturbances to open market operations also generates a persistent rise of nominal and real interest rates on securities in response to a monetary contraction. Furthermore, the introduction of staggered prices is demonstra-ted to improve the model's ability to replicate second moments of empirical time series.
Keywords: 330; Monetary policy; financial intermediation; open market operations; business cycles; price stickiness